Compare the Mean Duration of Active First Stage of Labour Among Primi Gravida Presenting at Term Treated with and Without Hyoscine - Sadia , Halima; Yahya, Wajeeha; Zakia , Syeda; Saeed , Saeeda; Naveed, Doha; Mazhar , Kinza (Indus Journal of Bioscience Research, 2025)
Introduction: Diagnosis of labour onset has been described as probably one of the most difficult decisions made by providers of maternity care. The first stage of labour addresses the goal of thinning or effacing the cervix; dilating or opening it for least 10 centimeters in size adequate for passage of the infant from uterus to the vagina. To compare mean duration of active first stage of labour of primigravida presented at term treated with and without hysocine. This study was a randomized controlled trial conducted at the Department of Gynae and Obstetrics, Pakistan Institute of Medical Sciences, Islamabad from July to December 2022. We studied 60 patients (30 per group) who were admitted for labor trial after obtaining their ethical approval. 20 mg IV hyoscine group received 20 mg hyoscine, while control group received none. Active labor duration was monitored. Results: Sixty women consented with an mean age of 25.50±3.45 years. The overall mean duration of the active phase of labour in hyoscine group was 212.62±25.01 minutes and significant (p-value = 0.025) reduction was observed in its duration of the first active stage when compared with conventional group. Maternal age, BMI and foetal weight were used to segregate duration of active stage of labour and there was no significant difference (p value > 0.05). Conclusion: Hyoscine decreases the duration of the active phase of labour in primigravdae without any side effects on the mother or or the neonate. Factors such as age of 35 years and above, higher BMI or neonatal weight had no effect on foetal outcomes.